Cancer Nanopharmaceuticals: Physicochemical Characterization and In Vitro/In Vivo Applications - Zielińska, Aleksandra (2021)
Physicochemical, pharmacokinetic, and biopharmaceutical characterization tools play a key role in the assessment of nanopharmaceuticals' potential imaging analysis and for site-specific delivery of anti-cancers to neoplastic cells/tissues. If diagnostic tools and therapeutic approaches are combined in one single nanoparticle, a new platform called nanotheragnostics is generated. Several analytical technologies allow us to characterize nanopharmaceuticals and nanoparticles and their properties so that they can be properly used in cancer therapy. This paper describes the role of multifunctional nanoparticles in cancer diagnosis and treatment, describing how nanotheragnostics can be useful in modern chemotherapy, and finally, the challenges associated with the commercialization of nanoparticles for cancer therapy.